Functional analysis of the C-reactive protein (CRP) gene -717A>G polymorphism associated with coronary heart disease - Chen Shufeng; Li Hongfan; Li Yun; Lu Xiangfeng; Wang Laiyuan; Gu Dongfeng (BMC, 2009)
Abstract Background Atherosclerosis underlies the major pathophysiological mechanisms of coronary heart disease (CHD), and inflammation contributes to all phases of atherosclerosis. C-reactive protein (CRP), a sensitive, but nonspecific marker of inflammation has been shown to play proatherogenic roles in the process of atherosclerosis. Our previous report showed that rs2794521 (-717A>G), located in the promoter of the CRP gene, was independently associated with CHD in Chinese subjects. In the present study, we tried to investigate the biological significance of this genetic variation in vitro. Methods The influence of G to A substitution at the site of rs2794521 on the transcriptional activity of the promoter of the CRP gene was assessed by luciferase reporter assay, and protein binding to the site of rs2794521 was detected by EMSA assay. Results The G to A exchange at the site of rs2794521 resulted in an increased transcriptional activity of the promoter of CRP gene, and glucocorticoid receptor (GR) protein factor bound drastically differently to the A and G alleles at the site of rs2794521. Conclusion These results provided functional evidence supporting the association of the SNP rs2794521 of the CRP gene with CHD probably through regulating the expression level of CRP by different variations of rs2794521.